Effects of Anterior Plating on Achieving Clinically Meaningful Improvement Following Single-Level Anterior Cervical Discectomy and Fusion - Conor P. Lynch; Elliot D.K. Cha; Madhav R. Patel; Caroline N. Jadczak; Shruthi Mohan; Cara E. Geoghegan; Kern Singh (Neurospine, 2022)
Objective The clinical utility of anterior cervical plating for anterior cervical discectomy and fusion (ACDF) procedures remains controversial. This study aims to compare the impact of cervical plating on achievement of minimum clinically important difference (MCID) up to 2 years following ACDF. Methods Patients undergoing primary, single-level ACDF procedures were grouped based on whether their procedure included application of an anterior cervical plate. Demographics, preoperative spinal diagnoses, operative characteristics, and patient-reported outcome measures (PROMs) were compared between plating groups. Achievement of an MCID was assessed using the following previously established thresholds: 12-item Short Form health survey physical component summary (SF-12 PCS) 8.1, visual analogue scale (VAS) neck 2.6, VAS arm 4.1, Neck Disability Index (NDI) 8.5. Rates of MCID achievement were compared between groups. Results The cohort included 192 patients of whom 102 received plating and 90 received no plating. Plating status was significantly associated with Charlson Comorbidity Index and insurance status. Operative duration and estimated blood loss were significantly greater for the plating group. Both groups demonstrated significant improvements at the majority of postoperative timepoints. Significant intergroup differences in PROM improvement were demonstrated for VAS neck and NDI at 6 weeks. Rates of MCID achievement differed significantly between groups for NDI at 6 weeks, and 12 weeks, and SF-12 PCS overall. Conclusion Patients improved significantly in terms of pain, disability and physical function, regardless of plating status, and with the exception of early neck pain and disability, these improvements were similar between groups. Patients that underwent plating as part of their ACDF procedure achieved an MCID for physical function at lower rates overall.